On the Nature of Philosophy and Other Philosophical Essays - Rescher, Nicholas (De Gruyter, 2021)
This book continues Rescher’s longstanding practice of publishing groups of philosophical essays. Notwithstanding their thematic diversity, these discussions exhibit a uniformity of method in addressing philosophical issues via a mixture of historical contextualization, analytical scrutiny, and common-sensical concern. Their interest, such as it is, lies not just in what they do but in how they do it.